Writing Yogis: Breathing Our Way to Mindfulness and Balance in Embodied Writing Pedagogy - Christy I. Wenger (Journal of the Assembly for Expanded Perspectives on Learning, 2012)
Breathing exercises constitute a method for helping students to attain a state of mindfulness in their writing—and their lives.